Hubungan Stimulasi Bahasa oleh Orang Tua terhadap Kemampuan Berbicara Anak Usia Dini di TK Dahlia Tapa - Sulastya Ningsih; Fidya Fidya; Dekfi Rajak; Abel Tombokan; Moh Bintang Dwi Putra; Amelia Putri Tahir (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2026)
This study aims to determine the effect of parental language stimulation on the speech skills of early childhood children at Dahlia Tapa Kindergarten. Speaking skills are a crucial aspect of children's language development, influenced by the quality of parental interaction and communication. This study used a quantitative approach with a correlational method. The study population was all early childhood children at Dahlia Tapa Kindergarten and their parents, with a sample size of 30 respondents. Data collection techniques included a questionnaire to measure parental language stimulation and an observation sheet to measure children's speech skills. Data were analyzed using descriptive statistics and simple regression. The results showed that parental language stimulation had a positive and significant effect on early childhood speech skills, with a correlation coefficient of 0.742 and a coefficient of determination of 55.1%. These findings suggest that the better the parental language stimulation, the better the children's speech skills. Therefore, active parental involvement is essential in supporting children's language development from an early age.